Penerapan Terapi Relaksasi Otot Progresif Masalah pada Keluarga dengan Diabetes Gangguan Kenyamanan - Febriani, Indra; Erman, Imelda; Yunisa, Yunisa; Endriyani, Sri; Athiutama, Ari (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Diabetes is a group of metabolic diseases characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or both. This case study uses a descriptive method with a nursing approach. This research was carried out from March 15 to March 21 2023 and continued from March 25 to March 31 2023. The research subjects were 2 people who were given nursing progressive muscle relaxation therapy for 6 consecutive days. This research was conducted in the work area of the Palembang Community Health Center. The research results after progressive muscle relaxation therapy showed that the client's comfort situation improved and showed significant differences in blood sugar levels on the first and sixth days after progressive muscle relaxation therapy. Client 1 was 242 mg/dL on day 1 and 200 mg/dL on day 6, while client 2 was 224 mg/dL on day 1 and dropped to 195 mg/dL on day 6. Sir. Conclusion: Progressive muscle relaxation can increase comfort and also reduce blood sugar in diabetes patients.